Self‐knotting of distal end of nasogastric tube—Not an uncommon possibility. Issue 2 (24th June 2020) - Kumar Sinha, Amit; Ahmad, Sohail; Rashi, Rashi; Kumar, Amit; Kumar, Bindey
ABSTRACT: Importance: A nasogastric tube is used commonly to decompress the stomach and provide enteral feeding in surgical and medical practice. Sometimes this safe and innocent‐looking tube may lead to unexpected complications. We focus here on the possibility of spontaneous 'lariat loop' knotting of the nasogastric tube when some resistance is felt on tube retrieval and describe a method of safe tube removal. Case presentation: We present a case of self‐knotting of a nasogastric tube that was placed to decompress the stomach during the postoperative period after surgical repair of anorectal malformation in a 4‐month‐old boy. Conclusion: Self‐knotting of the distal end of nasogastric tube is an unusual complication with catastrophic sequelae if not addressed properly. If any resistance is felt during nasogastric tube retrieval, self‐knotting of the tube must be suspected.